Supplementation of Mulberry leaf extract on growth performance and carcass percentage of broilers - Dwi Suryayuliana, Ifan; Agustin, Citravia; Prihtiyantoro, Wahyu (Jurnal Ilmu Peternakan Terapan, 2025)
The purpose of the study was to determine the effect of Mulberry leaf extract (MLE) supplementation in drinking water on growth performance and carcass percentage of broiler chickens. The research method is quantitative. The broilers were supplemented with MLE in drinking water for 28 days. The research consists of five treatments with four replications, T0 = drinking water (negative control), T1 = 0.05 g tetracycline antibiotics/liter of drinking water (positive control), T2 = 1 ml MLE/liter of drinking water, T3 = 3 ml MLE/liter of drinking water and T4 = 5 ml MLE/liter of drinking water. Research parameters include growth performance and carcass percentage. Data analysis was conducted using ANOVA, and it was followed by the Duncan test. The results of the study showed that supplementation of the extract in drinking water did not affect feed intake, water intake, non-carcass percentage, and abdominal fat, but affected the final weight, carcass percentage, and feed conversion ratio. The study concluded that the supplementation of MLE with a dose of 0.05 g/liter of drinking water increased final body weight, average daily gain, carcass percentage, and decreased feed conversion ratio of broilers.